Efficient certificateless designated verifier proxy signature scheme using UAV network for sustainable smart city. (May 2022) - Xu, Zhiyan; Luo, Min; Vijayakumar, Pandi; Peng, Cong; Wang, Lianhai
Abstract: Sustainable smart city idea is rapidly evolving with the aim of improving the quality of life of residents utilizing the integration of information and communication technologies(ICT) with state-of-the-art technology in practice. Unmanned aerial vehicle (UAV) technology has been widely used in sustainable smart city construction due to its advantages such as low price, good maneuverability and strong flexibility. However, as the heterogeneity of smart city systems and the high mobility of UAV network nodes cause them to face more serious security threats, ensuring the security and authenticity of message is crucial for UAVs to correctly perform the tasks issued by the command center. To fix the above-mentioned issues, many digital signature schemes have been presented in recent years. Regrettably, most existing schemes either have security vulnerabilities or poor performance. Very recently, He et al. came up with a certificateless designated verifier proxy signature (CLDVPS) scheme and advocated that it was secure. But, we find that their scheme cannot achieve its stated purpose because it fails to resist user impersonation attack. We put forward a new CLDVPS scheme to address the data security and privacy issues in UAV networks. Security analysis and performance evaluation show that our scheme can realize a higher security level while greatly reducing communication and computation overheads. Compared with related schemes, our scheme is more suitable for the application of UAV network in sustainable smart city. Highlights: We demonstrate a CLDVPS scheme cannot withstand the impersonation attack. We propose a new CLDVPS scheme to address the data security issues in UAV networks. New scheme can realize a higher security level while greatly reducing communication and computation overheads.